Developing ideation cards to support the design of mixed reality games - Wetzel, Richard (2017)
Mixed reality games combine interactive digital content with real world environments, objects, and actors by utilizing a multitude of different sensors. While offering plenty of opportunities for designers, they are also notoriously difficult to design. This is in part due to them still being a relatively new form of gaming with only very few examples of commercially successful games. This means that the majority of aspiring designers lacks knowledge about the design space of these games – something that is crucial in order to create new and exciting experiences. While there exist several authoring tools to facilitate the development of mixed reality games, these tools do not provide guidance on the game design aspects. The design of mixed reality games is likewise bringing together experts from different domains (e.g. game design, technology, locales). In order to support this multifaceted and collaborative design process I have developed the Mixed Reality Game Cards. These are a deck of ideation cards that encapsulate the design space of mixed reality games in the form of physical playing cards. The cards can be used for rapid idea generation (i.e. creating a multitude of ideas from scratch in a short time) and in-depth idea development (i.e. further expanding and refining an idea). The Mixed Reality Game Cards consist of four types of cards to support idea generation as well as idea development. Opportunity Cards are the building blocks of an idea and describe potential elements of a design. Question Cards prompt the design group to consider the experience from different angles to refine the design. Challenge Cards surface typical design issues and problems that might occur. These domain-specific cards are supported by Theme Cards that are taken from the board game Dixit in order to provide additional domain-extrinsic sources of inspiration. I developed the Mixed Reality Game Cards iteratively over the course of seven studies following a Research through Design approach. This provided valuable insight into what makes ideation cards such powerful facilitators of collaborative design sessions. I identify content, appearance, and rules as crucial elements under direct control of an ideation card designer and tangible as well as playful interactions as dynamics that emerge during an ideation session. This thesis describes the development of the Mixed Reality Game Cards and uses the insights gained from this process to reflect on ideation cards as design tools in general, expanding our understanding of them.